Youth Participation as Non-State Actors in Supporting Urban Waste Management Through Student Waste Bank - Fuzy Firda Zhan; Hani Alfiyani; Hartady, Novizar (International Journal of Sustainable Applied Sciences, 2024)
The Waste Bank is a banking concept by saving waste whose aim is not only to increase the incentives of the user community, but the main thing is as an effort to overcome problems related to waste management. The 3R (reduce, reuse, and recycle) culture should be implemented and become a habit for all levels of society. Because if you don't get used to it immediately, it will have an impact on more and more waste going to the Final Processing Site. One of these problems occurs in Pontianak City. The waste that enters the Batu Layang Final Processing Site reaches 285 tons per day in period I of 2022. This is triggered by the still not massive 3R culture and waste segregation using the Waste Bank. This problem is not only the responsibility of state actors but also non-state actors, one of which is the younger generation. This research was conducted to analyze the participation of youth as non-state actors to overcome waste management problems through the Student Waste Bank program. The method used in this research is descriptive with a qualitative approach. The data in this study were collected from literature studies and documentation studies. The results of this study found that efforts to preserve a sustainable environment have been pursued by the younger generation through the Student Waste Bank as carried out by students and alumni of Universitas Tanjungpura which has been synergistically initiated since 2021 until now. The recommendations from this research are for the government, academia, and institutions to work together synergistically to support the cultivation of 3R and the optimal use of the Waste Bank by the community.